Evaluation of the use of tacrolimus ointment for the prevention of hypertrophic scars in experimental model - Mariana Campos Souza Menezes; Leonardo de Souza Vasconcellos; Cristiana Buzelin Nunes; Luiz Ronaldo Alberti
Abstract BACKGROUND: Tacrolimus, for its activity on modulation of collagen production and fibroblast activity, may have a role in the prevention of hypertrophic scars. OBJECTIVES: Evaluate macroscopic, microscopic, metabolic, laboratory effects and side effects of the use of topical tacrolimus ointment, in different concentrations, in the prevention of hypertrophic scars. METHODS: Twenty-two rabbits were submitted to the excision of 2 fragments of 1 cm of each ear, 4 cm apart, down to cartilage. The left ear of the animals was standardized as control and Vaseline applied twice a day. The right ear received tacrolimus ointment, at concentrations of 0.1% on the upper wound and 0.03% on the lower wound, also applied twice a day. Macroscopic, microscopic, laboratory criteria and the animals' weight were evaluated after 30 days of the experiment. RESULTS: Wounds treated with tacrolimus, at concentrations of 0.1% and 0.03%, when compared to control, showed a lower average degree of thickening (p = 0.048 and p <0.001, respectively). The average of scar thickness and lymphocyte, neutrophil and eosinophil concentrations are lower in the treated wounds compared to the control (p <0.001, p=0.022, p=0.007, p=0.044, respectively). The mean concentration of lymphocytes is lower in wounds treated with a higher concentration of the drug (p=0.01). STUDY LIMITATIONS: experiment lasted only 30 days. CONCLUSIONS: Tacrolimus at the 2 concentrations evaluated reduced the severity of inflammatory changes and positively altered the macroscopic aspect of the scar in the short term. Its use was shown to be safe, with no evidence of systemic or local adverse effects.